Analysis of Security and Performance Service in Service Oriented Architecture (SOA) and Data Integration - Erick Fernando; Hetty Rohayani. AH; Pandapotan Siagian; Derist Touriano (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
Nowdays, the use of web services in the world of education is very much particular services and information provided in the form of the transaction until the payment - the payment and security in a system that is built in the form of a website. This system does not yet have a system that is integrated with each other and the security that is necessary to develop a system that leads towards it. Services provided requires an integrated system of all related system, the Service Oriented Architecture (SOA) to be used as an efficient solution for integrating distributed applications. In SOA-based environment that focuses on quality of service called WSARCH (Web Services Architecture). With this paper can then propose a system that uses a Service Oriented Architecture (SOA) with Web Services Architecture to resolve accurately than techniques that have a lower negative impact in terms of service performance and security.